Inuit Symbolism of the Bearded Seal - Sonne, Birgitte (Études/Inuit/Studies, 2017)
The skins of the bearded seal—both dress and interior skins—were indispensable in Inuit/Yupiit technology. Converted into straps, thongs, covers, pokes, rain clothing, and underwear, the skins served to make transport possible, facilitate hunting activities, and protect people against wet and stormy weather. Similarly, the same skin objects permitted contact and exchanges with the beings of the Other Worlds, on which the earthly life of humans depended. Symbolic analysis of the characteristics of bearded seal as reflected in ritual, myth, and sayings reveals that bearded seal turns out to bear both frightening and beneficial meanings. Feared in the figure of a bogey at the height of winter, welcomed as the first seal to arrive from a great distance in early spring, inspiring reproduction and protecting Raven in renewing the earth at equinoxes, bearded seal made the Inuit/Yupiit world cohere. Les peaux du phoque barbu étaient indispensables dans la technologie Inuit/Yupiit. Converties en lanières, sangles, housses, vêtements de pluie et sous-vêtements, les peaux servaient à rendre le transport possible, à faciliter les activités de chasse et à protéger les personnes contre les intempéries. Ces mêmes objets de peaux permettaient le contact et les échanges avec les êtres des Autres Mondes, dont dépendait la vie terrestre de l’homme. L’analyse symbolique des caractéristiques du phoque barbu, telle que reflétée dans les rituels, les mythes et les dictons, révèle que le phoque barbu s’avère avoir des significations à la fois effrayantes et bénéfiques. Craint sous la forme d’un spectre au plus fort de l’hiver, accueilli comme le premier phoque arrivé de très loin au début du printemps, inspirant la reproduction et protégeant Corbeau en renouvelant la terre aux équinoxes, le phoque barbu assure la cohérence du monde Inuit/Yupiit.